Housing Policy in the Political Agenda: The Trajectory of Portugal - Allegra, Marco (2022)
Housing policy, a field located at the junction between welfare and spatial planning, is a key component of urban agendas. This chapter refers to the trajectory of housing policy in Portugal exploring how, and to what extent, housing has constituted a growing matter of political attention, in a country that—formally—has no urban agenda, but where significant interventions in the housing sector have occurred in recent times. We explore how housing policy has changed over the last four decades by adopting a multi-scalar perspective on the governance of the housing sector, in order to show how many different actors (central and local governments, policy experts, activists, etc.) and contingent events (such as the post-2008 economic crisis or the COVID-19 pandemic, whose full impact on housing policy is already evident but still difficult to grasp) have influenced these dynamics. This chapter proposes a genealogy of the emergence of the idea of “housing policy” as a matter of political attention in its own right and its status as a component in the country’s urban agenda. A key focus of the analysis will be the relationship that has developed between Portugal and the EU—from the country’s adhesion to the European Economic Community (1986) to the programme Next Generation EU (2020).